A Computational Intelligent Algorithm For Solving Unit Commitment Problem - Aiza Nazifa Binti Mohd Zahari (2023)
Unit Commitment (UC) is the task in finding the most optimum generating schedule of each generating unit. In determining UC, Distributed Generation (DG) would be one of the factors that would influence the outcome of power generation as it would deploy small – scaled technologies nearer to consumers. It would be able to compensate on shortcomings of the power network i.e. power shortage or line interruption. A traditional DG layout would require the use of only Non – Renewable Energy source (NREs) such as coal that would have a significant impact on the environment. This paper will be focusing on the integration of Renewable Energy Source (RES) which is Solar and NREs which would be Micro Gas Turbine (MGT) into the DG layout with the use of Mixed Integer Linear Programming (MILP) to solve the mathematical problem. The integration of both energy source would reduce the operational cost. Results obtained would also support that the power output from this planning would be able to meet with the ever changing load demands.